1989
DOI: 10.1111/j.1349-7006.1989.tb02304.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Monoclonal Antibodies against Cytokeratin 18 Generated from Patients with Gastric Cancer

Abstract: By co‐culturing regional lymph node B‐cells and HAT‐sensitive mutant cells obtained from RPMI‐1788 cells, no less than 20,000 Epstein‐Barr (EB)‐transformed colonies were obtained from 32 patients with gastric cancer. From B‐cell cultures generating antibodies reactive with gastric cancer tissues as well as cultured gastric cancer cells, two EB‐transformed cell clones termed C418–59 and C1218–39 were isolated. Both of them produced human IgM‐class antibodies, termed Mab418–59 and Mab 1218–39, respectively. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Circulating anti-cytokeratin 8 antibody immune complexes were reported in sera of patients with pulmonary fibrosis (30). The presence of autoantibodies directed against cytokeratin 18 has been observed in sera from patients with gastric cancer (31). Interestingly, transgenic mice that express a mutant form of cytokeratin 18 develop chronic hepatitis with a disruption of hepatocyte keratin filaments (32).…”
Section: Tumor Antigens In Liver Cancermentioning
confidence: 99%
“…Circulating anti-cytokeratin 8 antibody immune complexes were reported in sera of patients with pulmonary fibrosis (30). The presence of autoantibodies directed against cytokeratin 18 has been observed in sera from patients with gastric cancer (31). Interestingly, transgenic mice that express a mutant form of cytokeratin 18 develop chronic hepatitis with a disruption of hepatocyte keratin filaments (32).…”
Section: Tumor Antigens In Liver Cancermentioning
confidence: 99%
“…Although there has been an important decline in mortality rates in recent years, there remains a high recurrence rate following primary therapy. Previously, it was reported that CK-18 expression was detected in tissue blocks of some patients with gastric carcinoma [13] . Recently, Xu et al [14] showed that gastric carcinoma patients had over-expression of CK-18 mRNA while patients with benign gastric pathologies such as gastric ulcers did not.…”
Section: Introductionmentioning
confidence: 99%
“…RS-11 was developed by immunization of rats with a syngeneic bladder tumor and its isotype is IgM. Interestingly, there are several reports that mAbs generated using autologous lymphocytes of tumor-bearing patients recognize keratin 8 or keratin 18 (35)(36)(37)(38). The isotypes of these mAbs are all IgM.…”
Section: Discussionmentioning
confidence: 99%